PERANCANGAN MEDIA KATALOG SEBAGAI PENUNJANG INFORMASI DAN PROMOSI PADA CV.ZERO STORE - Dewi Immaniar Desrianti; Anita B Wandanaya; Asih Sumaryani (Universitas Raharja, 2014)
With the development of computer technology , especially in the field of multimedia enabling competition in the highly competitive retail world . At the present time due to intense competition in the business world , the service and quality of goods is not enough to be able to increase revenue and attract customers who are loyal and inevitably this makes employers think hard to find a way to survive and stable in the business . One way is to use visual communication media can indirectly communicate the expected value of its effectiveness in product marketing programs . CV.Zero Store is a company located in Villa Mutiara Pluit Tangerang which sells a variety of products and a jersey type shirt screen printing . The problems that exist in the company does not have a means of supporting media promotion of effective programs , this company is already using a media campaign to promote its products as it is used today is the brochures , banners , promotions with clients directly keklien and perceived inadequate for future promotion . Therefore , it takes promosiyang other means such as the media in the desired catalog marketing targets that have been programmed . For media catalog is a masterpiece of design that is packaged in the form of a booklet which is a medium that can be made in the company’s assets that can be used to improve an image or the image of the company to establish cooperation relations with companies , institutions and other relevant agencies . Besides the new design is expected to add variants of the media campaign so as to form the image or the image of the company as desired . Therefore dituangkanlah such a design in an article entitled “Designing Catalog For Supporting Information Media and Promotions at CV Zero.Store “